Experimental practice technoscience, alterontologies, and more-than-social movements - Papadopoulos, Dimitris (Experimental futures, 2018)
Decolonial politics of matter -- Biofinancialization as terraformation -- Ontological organizing -- Activist materialism -- Insurgent posthumanism -- Brain matter -- Compositional technoscience -- Crafting ontologies